PERAN INFLUENCER DAN UANG SAKU GENERASI MUDA DALAM BERBELANJA ONLINE - Wahab, Wirdayani (Komunitas Manajemen Kompetitif, 2024)
The role of influencers and pocket money of the younger generation in online shopping has a close relationship, especially in the current digital era. This study aims to prove whether pocket money has a role in the influence of influencers on the online shopping decisions of the younger generation. Using a quantitative method with a sample of the younger generation in Pekanbaru city totaling 100 people and taken randomly. The results of the study prove that influencers are often a source of shopping inspiration, especially through product reviews, unboxing, or direct promotions. The younger generation tends to trust recommendations from influencers they idolize. Pocket money determines how much the younger generation can fulfill their desires which are influenced by influencer promotions.